Surgical management of impacted mandibular premolar - Orsola Brucoli; Eleonora Rivetti; Paolo Boffano (DiscoverSys Inc., 2021)
The impaction of mandibular premolars is a challenging complication in tooth eruption. The arrested eruption of the lower premolars can determine disturbances of mastication and aesthetics. Moreover, the frequent tight relationship between the impacted premolar and the inferior alveolar nerve makes the management of this condition extremely difficult. In this article, we report the management and the outcome of the surgical treatment of an unusual case of impacted mandibular premolar.